Missionary cosmopolitanism in nineteenth-century British literature - Werner, Winter Jade (Literature, religion, and postsecular studies., 2020)
"Examines the effects of missionary evangelicalism on cosmopolitanism through the nineteenth-century novel, including works such as Charlotte Brontë's Jane Eyre, Charles Dickens's Bleak House, and lesser-known works by Robert Southey and Sydney Owenson"--